2011
DOI: 10.1007/s10722-011-9686-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Bambara groundnut (Vigna subterranea (L.) Verdc.) as revealed by phenotypic descriptors and DArT marker analysis

Abstract: Genetic diversity of a Bambara groundnut germplasm representing accessions from 25 African countries, maintained at the International Institute of Tropical Agriculture (IITA; Nigeria) was evaluated based on seed patterns, qualitative characters, quantitative traits and Diversity Arrays Technique (DArT) markers. The study aimed at identifying important descriptors for germplasm conservation, validating the crop's geographical centre of origin and facilitating the utilization of existing genetic resources. Frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
86
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(100 citation statements)
references
References 15 publications
10
86
1
3
Order By: Relevance
“…Research focusing on inter and intra-landrace variation for phenotypic descriptors (either as an independent study or as part of a broader characterization of germplasm) has been extensively reported in Bambara groundnut (Goli 1995;Karikari and Tabona 2004;Ntundu et al 2006;Ouedraogo et al 2008;Abu and Buah 2011;Olukolu et al 2012;Touré et al 2012;Aliyu and Massawe 2013;Shego et al 2013;Molosiwa et al 2015). While most of these reports have been largely country specific, a few have a global germplasm diversity perspective (including landraces from the major agro-ecologies across Africa and Southeast Asia; Goli 1995;Olukolu et al 2012;Molosiwa 2012;Molosiwa et al 2015).…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 99%
See 4 more Smart Citations
“…Research focusing on inter and intra-landrace variation for phenotypic descriptors (either as an independent study or as part of a broader characterization of germplasm) has been extensively reported in Bambara groundnut (Goli 1995;Karikari and Tabona 2004;Ntundu et al 2006;Ouedraogo et al 2008;Abu and Buah 2011;Olukolu et al 2012;Touré et al 2012;Aliyu and Massawe 2013;Shego et al 2013;Molosiwa et al 2015). While most of these reports have been largely country specific, a few have a global germplasm diversity perspective (including landraces from the major agro-ecologies across Africa and Southeast Asia; Goli 1995;Olukolu et al 2012;Molosiwa 2012;Molosiwa et al 2015).…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 99%
“…While most of these reports have been largely country specific, a few have a global germplasm diversity perspective (including landraces from the major agro-ecologies across Africa and Southeast Asia; Goli 1995;Olukolu et al 2012;Molosiwa 2012;Molosiwa et al 2015). The standard descriptors for Bambara groundnut [International Plant Genetic Resources Institute/International Institute of Tropical Agriculture/The International Bambara groundnut Network (IPGRI/IITA/BAMNET 2000)] have been used as guidelines in these phenotypic characterization exercises.…”
Section: Overview Of Qualitative and Quantitative Phenotypic Diversitmentioning
confidence: 99%
See 3 more Smart Citations